The impact of mining on the economic and social development of the southern region of Peru from 2007 to 2020 - Escudero Simon, William (2023)
The mining industry is an important support of the economy and development of Peru, consequently the research work aims to establish the impact of mining on the economic and social development of the southern region from 2007 to 2020. In the research work was used statistical tools, secondary data was collected from national agencies, such as the Central Reserve Bank, National Institute of Statistics, and Informatics; Ministry of Labor and Employment Promotion, Ministry of Labor and Employment Promotion, on the economic and social aspect of Peru during 2007 to 2022. The statistical results of the research conclude that mining analyzed in its different dimensions impacts on the social economic development of the southern regions of Peru.To strengthen the sustained impact of mining on the economic and social development of the southern region of Peru, initiatives are planned to increase the impact of mining, through a multidisciplinary team of professionals with experience in project management, who will manage the allocation of monetary resources generated by mining, also the multidisciplinary team should also be under the control of the Ministry of Economy and Finance.The Peruvian state, through the multidisciplinary team of professionals responsible for managing the resources that come from the mining sector, must plan scheduled meetings with the representatives of regions to review the budgets, expenses of the investments that are being made in the infrastructure works, schools, hospitals that are being carried out sustainably over time for the economic and social development of the region and the country.